The effect of spatial and visual configuration of museums in the formation of visiting patterns - Alkurukchi, Miqdam A. M. (Iraqi Journal of Architecture and Planning)
Museums add cultural and social values to their societies, by transferring knowledge to the visitors through their exhibits. Accordingly, movement/visibility relation is considered as a crucial aspect in explaining spatial manners of museums, and direct operator in the formation of visiting patterns. The relation between both faces of museum’s spatial configuration (movement axes, and visibility network), represents phenomena that lacks adequate research endeavors, despite its importance in the formation of visiting experiment patterns. Accordingly, the study aims to explain this relation. Using the comparative analysis methodology between Iraqi and international museum buildings. The results show full coincidence of the most integrated movement axes with the most integrated visibility areas, in some cases. And partial coincidence in others. With special syntactic position for Gathering Spaces in Museums.